Developing a new model to predict the diurnal water demand pattern for residential areas subjected to formal intermittent supply in South Africa - Msutu, Thembela Lumumba (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.